Metabolic and antioxidant effects of inoculation with arbuscular mycorrhizal fungi in crops of flesh‐coloured Solanum tuberosum treated with fungicides. (21st October 2021) - Alarcón, Sebastián; Tereucán, Gonzalo; Cornejo, Pablo; Contreras, Boris; Ruiz, Antonieta
Abstract: BACKGROUND: Solanum tuberosum tubers have higher content of phenolic compounds such as hydroxycinnamic acid derivatives (HCAD) and anthocyanins in coloured genotypes. The use of fungicides for crops is common, but there are few studies regarding the interaction of fungicides and arbuscular mycorrhizal fungi (AMF). Here, the AMF–plant interactions and the metabolic responses of three potato genotypes with different tuber colorations (VR808, CB2011‐509 and CB2011‐104) inoculated with Claroideoglomus claroideum (CC), Claroideoglomus lamellosum (HMC26) or Funneliformis mosseae (HMC7) were studied together with the use of the fungicides MONCUT (M) and ReflectXtra (R). Mycorrhizal traits, phenolic compound profiles and antioxidant activity (AA) were evaluated. RESULTS: Despite only two HCADs being identified, with 5‐caffeolquinic acid the most abundant, four anthocyanins were detected only in purple potato genotypes. The anthocyanin and HCAD profiles, as well as AA, showed that the CB2011‐104 genotype had better characteristics than the other genotypes, while VR808 and CB509 showed similar responses. The responses were dependent on the specific combinations of genotype, fungicide and the AMF strain, and generally showed better responses when colonized by AMFs. CONCLUSION: The three potato genotypes had differential responses depending on the inoculated AMFs and the fungicide applied before sowing, where the optimal combinations for antioxidant response, mycorrhization degree and performance were HMC26/R for VR808, HMC7/M for CB2011‐509 and HMC26/M for CB2011‐104. Our results suggest the existence of functional compatibility that can be registered as beneficial effects even at the genotypic level of the host regarding a specific AMF strain. © 2021 Society of Chemical Industry.